BUILDING INTERFAITH SOLIDARITY DURING THE COVID-19 PANDEMIC THROUGH CELEBRATION OF MUSLIM AND CHRISTIAN RELIGIOUS HOLIDAYS IN INDONESIA - Maftukha Maftukha (Jurnal Sosiologi Reflektif, 2022)
Physical distancing policy has forced religious people in Indonesia to carry out worship at home and celebrate religious holidays with following a strict health protocol. This situation has affected for a loosening of solidarity in society, especially at the beginning era of pandemic. However, there are religious groups that modify some of the practices of religious rituals on their religious holidays, and adapt them to the rules of physical distancing, including Muslims and Christians in North Sulawesi. This article intends to discuss about Lebaran Ketupat and Thanksgiving, which are Muslim and Christian holidays in Minahasa as a means to strengthen community solidarity during the pandemic. This article was compiled based on a qualitative approach with data collection techniques in the form of in-depth interviews with Muslim and Christian communities in Ratatotok, Southeast Minahasa and Poigar Bolaang Mongondow in North Sulawesi. The results showed that the practice of Lebaran Ketupat and Thanksgiving can create social solidarity among interfaith groups. In addition, modifications to the practice of Eid Ketupat and Thanksgiving during the 2020-2021 pandemic have become a local resilience in dealing with the various impacts of the Covid-19 pandemic. Their ability to modify the Lebaran Ketupat and Thanksgiving rituals allows Muslim and Christian communities to create their solidarity as “torang samua basudara” (we are all brothers), in both idea and practice.Physical distancing telah memaksa umat beragama di Indonesia untuk melaksanakan ibadah di rumah dan merayakan hari besar keagamaan dengan protokol kesehatan yang ketat. Hal ini berimplikasi pada mulai merenggangnya solidaritas di masyarakat. Namun demikian, terdapat kelompok keagamaan yang memodifikasi beberapa praktik ritual keagamaan pada hari besar keagamaan mereka, dan menyesuaikannya dengan  aturan pembatasan physical distancing tersebut, diantaranya adalah umat Muslim dan Kristen di Sulawesi Utara. Artikel ini bermaksud untuk membahas tentang Lebaran Ketupat dan Pengucapan Syukur yang merupakan hari besar umat Muslim dan Nasrani di Minahasa sebagai sarana untuk memperkuat solidaritas masyarakat di masa pandemi. Artikel ini disusun berdasarkan pendekatan kualitatif dengan teknik pengumpulan data berupa wawancara mandalam terhadap masyarakat Muslim dan Kristen di Ratatotok Minahasa Tenggara dan Poigar Bolaang Mongondow di Sulawesi Utara.  Hasil penelitian menunjukkan bahwa praktik Lebaran Ketupat dan Pengucapan Syukur dapat menciptakan solidaritas sosial diantara kelompok lintas agama. Selain itu, modifikasi praktik Lebaran Ketupat dan Pengucapan Syukur di masa pandemi pada tahun 2020-2021 telah menjadi local resilience dalam menghadapi berbagai dampak pandemi Covid-19. Kemampuan mereka untuk memodifikasi ritual Lebaran Ketupat dan Pengucapan Syukur memungkinkan masyarakat Muslim dan Kristen untuk menciptakan solidaritas mereka sebagai “torang samua basudara” (kita semua bersaudara), baik dalam ide maupun praktik.